Exploring Learning Difficulties in Civilisation Classes Case Study: First Year Students Department of English, Amar Thelidji-Laghouat - BRAHIMI ,Mohamed; BEN REDDA ,Djamel (Faculty of Letters and Foreign Languages Department of English, 2018)
Nowadays, the acquisition of foreign languages plays an important role in developing learners’ intercultural communication. Therefore, the teaching modules such as civilisation within the English studies at the Algerian universities are a paramount to strengthen this role. It offers students information on the main aspects of target language natives’ life. It also provides them with cultural background in order to prepare them for potential cross-cultural communication in which they may encounter linguistic and cultural barriers. Yet, in this specific context, we found that in the department of English at Amar Thelidji University (Laghouat) this goal is somehow difficult to reach. Therefore, this research aims at contributing to the existence of the solid link between language and culture by presenting comprehensive accounts to the didactic situations of teaching and learning civilisation in the department of English at Amar Thelidji University (Laghouat). It also identifies the difficulties and challenges that hamper the goal of this syllabus from being fully realised. The theoretical bases selected for the purpose were put according to descriptive method. Relying on the collected data from the tools used for the purpose, namely the teachers’ and students’ questionnaires. The research will provide some solutions for the major difficulties that face the learners by presenting some effective teaching techniques